Can Tax Simplification Help Lower Tax Corruption? - Awasthi, Rajul; Bayraktar, Nihal (World Bank Group, Washington, DC, 2014)
This paper seeks to find empirical evidence of a link between tax simplification and corruption in tax administration. It attempts to do this by first defining "tax simplicity" as a measurable variable and exploring empirical relationships between simpler tax regimes and corruption in tax administration. Corruption in tax administration is calculated with data series from the World Bank's Enterprise Survey Database. The focus is on business taxes. The study includes 104 countries from different income groups and regions of the world. The time period is 2002-12. The empirical findings support the existence of a significant link between the measure of tax corruption and tax simplicity, so a less complex tax system is shown to be associated with lower corruption in tax administration. It is predicted that the combined effect of a 10 percent reduction in both the number of payments and the time to comply with tax requirements can lower tax corruption by 9.64 percent. Some interesting regional differences are observed in the results. Similarly, the income level of countries plays an important role in determining the impact of tax simplification on tax corruption; specifically, the link is stronger for lower-income level countries. The positive link between tax simplicity and lower tax corruption has useful policy implications.